Stability analysis for a rotor system in a magnetically suspended control and sensitive gyroscope with the Lorentz force magnetic bearing rotation. (May 2019) - Xia, Changfeng; Cai, Yuanwen; Ren, Yuan
In order to intuitively and conveniently analyse the stability of a rotor system in a magnetically suspended control and sensitive gyroscope with the rotation of a Lorentz force magnetic bearing, this study proposes a stability analysis method on the basis of a pseudo-linear equivalent transformation and extended double-frequency Bode diagram. The working principle of the rotor system is presented, and the dynamic model for this system that considers the Lorentz force magnetic bearing rotation is established. The established real-coefficient two-input–two-output nonlinear system is transferred into a complex-coefficient single-input–single-output nonlinear system through variable reconstruction. Based on the complex frequency shift characteristics of Laplace transformation, the time-varying nonlinear system is converted into a pseudo-linear system. In accordance with the relationship between a Nyquist curve and a Bode diagram, the extended double-frequency Bode diagram method is proposed to analyse the stability of a non-minimum phase system with integral items. Simulation and experimental results demonstrate the correctness of the proposed analysis method.